Community Economic Evaluation and Sample Distribution of a State Park: The Case of the Belum Royal State Park, Malaysia - Dayang Affizzah, Awang Marikan; Norimah, Rambeli; Nur Ain, Azman; Mohamad Rohieszan, Ramdan (KODISA, 2022)
Purpose: This study was conducted to gauge the economic evaluation and sample distribution of conserving the Belum Royal State Park (BRSP) in Perak, Malaysia and to identify factors influencing its use by the community. This study aims to examine community perception on the conservation of the Belum Royal State Park (BRSP) and maximum community’s willingness to pay for park entry permits fees. Research design, data and methodology: A questionnaire survey was conducted involving a total of 280 respondents. The study adopted the Dichotomous Choice Contingent Valuation Approach (DC-CVM) and the Logistic Model, to estimate the maximum community’s willingness to pay for park entry permits fees. Results: The results established that the factors of respondent’s occupation, income, ecotourism influence on the BRSP and maximum entry price, significantly influenced visitors’ decision on community’s willingness to pay. The average community’s willingness to pay was RM9.68 per person. Conclusions: In conclusion, surveillance and patrols in protected areas should be expanded. The extra expense for ensuring safety can be offset through income from ecotourism that should also benefit the local community on economic evaluation and equal distribution on the BRSP.